Organizational prerequisites for the transition of companies towards a green economy - KRASIN, Miren (Edelweiss Applied Science and Technology, 2025)
The idea of an environmentally friendly, competitive, and green economy as a path to achieving sustainable development and rational use of resources is an important strategic measure of the EU. To implement this transition, organizations must have the necessary capacity for this purpose. Its creation and implementation are determined by numerous factors and certain organizational characteristics that they must possess to gradually build. Only in this way can the activities for the creation and use of “green” practices be guaranteed. The article aims to reveal the essence of the green economy approach and its characteristics in the context of sustainable development. In addition, it aims to determine and indicate the necessary prerequisites for building the required capacity of organizations to create conditions and attitudes for implementing this green transition. The method proposed and used by the author for studying and presenting dependencies and interrelationships favors the development of current and practically applicable solutions for the effective organization of work in companies to fulfill the tasks set in this direction.